To study demographic profile, risk stratification, and response to treatment in chronic myeloid leukemia patients - Manish Chandey; Rajandeep Kaur; Rajeev Gupta; Gurinder Mohan (APIK Journal of Internal Medicine, 2024)
Background: Chronic myeloid leukemia (CML) is the most common leukemia in India. The annual incidence of CML in India was originally reported to be 0.82.2 per 100,000 population. CML is a clonal disorder that is usually easily diagnosed by the Philadelphia chromosome. The approval of tyrosine kinase inhibitors has significantly reduced the mortality rate associated with CML and revolutionized treatment. Materials and Methods: Eighty patients diagnosed with CML were studied. Investigations were done and with European Treatment and Outcome Study (EUTOS) patients were stratified into low- and high-risk group and then treatment with Imatinib was given to all patients and molecular response was evaluated. Results: In the study population, out of 80 patients, 40 were female and 40 were male with M: F is 1:1. Out of total 80 patients', maximum patients (54) were in 31-60 years age group. Our study showed that the most common symptom of presentation is abdominal discomfort followed by fever. Out of total 80 patients, 25 (31.3%) patients had high EUTOS score and 55 (68.8%) patients had low EUTOS score. On 6 months' follow-up, 36.3% patients had complete molecular response, 16.3% patients had major molecular response and 47.5% patients had no molecular response, but on 12 months' follow-up, 71.3% patients had complete molecular response, 16.25% patients had major molecular response, and 12.5% patients had no molecular response. Conclusion: In this observational study, we found a significant correlation between EUTOS score and molecular response at 6 months and 12 months follow-up after Imatinib therapy.